(untitled) (International Seven Journal of Multidisciplinary, 2023)
In contemporary times, the so-called Information Society progressively forces us to walk in new directions, that is, we are changing our lives and activities due to the technological world. Such changes have reached schools, especially classrooms, which have been undergoing transformations to keep pace with the new Digital Information and Communication Technologies (ICT). In this wave came the applications called Apps, which have several features. Among them, we have Kahoot, which is an application that makes use of gamification to promote and evaluate learning. This research is qualitative in nature and its objective is to verify the use of the Kahoot application for science teacher training, and also to verify the efficiency of teaching chemistry, physics, and biology through this application. The results showed that Kahoot is effective in the teaching-learning process; however, it is necessary to have more investment policies for teacher training and further research in this area. DOI: 10.56238/isevmjv1n1-003